Clinical aspects of endothelial NO-synthase gene polymorphism in professional sportsmen (literature review) - S. N. Malakhova (Zaporozhye State Medical University, 2016)
The article deals the questions of properties and biological role of nitric oxide molecule, which is characterized with vasodilating, stress limiting and neurotransmitter properties, and participates in reactions of oxidative stress, glutamate and calcium cascade and inflammation. Researches of the relationship of endothelial NO-synthase and the risk of cardiovascular, ischemic and respiratory diseases in population of untrained persons and athletes continue. The aim of this study was to establish, according to the literature, the present state of the influence of endothelial NO-synthase gene polymorphism on the formation of the physical qualities of strength, endurance and speed in professional athletes, its changes and influence on functional state of athlete. At the present stage of development of medical genetics it is proved, that the implementation of the action of each individual isoform of the enzyme NO-synthase is caused by the presence of polymorphism. The most studied are the T-786С polymorphism of the eNOS gene promoter, G894T (Glu298Asp) polymorphism of the 7th exon, 4a/b-4th intron of eNOS, but their influence is not definitively proven, and is caused by the presence of homo- or heterozygotes. Genetic researches among professional athletes prove the significant role of nitric oxide system in enhancing of physical working capacity, but do not allow evaluating the characteristics of this effect, taking into account multi-directional training process and the level of sports qualification, as well as predicting future professional success and the preservation of the proper functioning of the cardiovascular, respiratory and other body systems. Conclusions. Thus, contemporary researches allow stating that oxide synthesis has a leading role in the functioning of the organism, and in particular athletes, but do not allow assessing its effects on the body of athletes of different sports qualification. It is proved that polymorphism of the eNOS gene is associated with ischemic disease, early development of atherosclerosis, a violation of endothelium-dependent vasodilation, diseases of the respiratory system and other changes in the body. But the question about changes in the functional state of the athletes of various sports qualification, depending on the polymorphism of endothelial NO-synthase, remains poorly understood.